(untitled) (Vietnam Journal of Community Medicine, 2022)
Report a rare case of cardiorrhexis: A 14 month-old patient with a cardiorrhexis was succesfully operated at Nghe An Obstetrics and Pediatrics Hospital. The surgery is supported by the external circulation extracoporelle. Cardiorrhexis in children is a rare injury. The diagnosis and treatment of cardiorrhexis is difficult. However, the patient can still be timely rescued.